2017
DOI: 10.1017/s0950268817002746
|View full text |Cite
|
Sign up to set email alerts
|

The impact of implementing a Xpert MTB/RIF algorithm on drug-sensitive pulmonary tuberculosis: a retrospective analysis

Abstract: Xpert MTB/RIF (Xpert) is the preferred first-line test for all persons with tuberculosis (TB) symptoms in South Africa in line with a diagnostic algorithm. This study evaluates pre- and post-implementation trends in diagnostic practices for drug-sensitive, pulmonary TB in adults in an operational setting, following the introduction of the Xpert-based algorithm. We retrospectively analysed data from the national TB database for Greater Tzaneen sub-district, Limpopo Province. Trends in a number of cases, diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Implementation of the Xpert MTB/RIF assay in various settings has been shown to significantly reduce time to diagnosis, as well as times to first-/second-line treatment initiation and time from diagnosis to negative culture conversion, but data with regard to its impact on treatment outcomes has so far been controversial [28,29]. In a large retrospective study conducted in South Africa, a reduction in the mortality rate in drug-susceptible patients from 14.9% to 9.8% (p <0.001) as well as improvement in treatment success from 71.4 to 84.6% (p <0.001) was seen after 5 years of using Xpert in TB diagnosis [30]. In other studies conducted in settings with medium and high TB and MDR-TB incidence, including one report from Kyiv (Ukraine), routine use of the Xpert MTB/RIF assay was not associated with better outcomes, or only marginal improvements have been observed [7e9,29].…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the Xpert MTB/RIF assay in various settings has been shown to significantly reduce time to diagnosis, as well as times to first-/second-line treatment initiation and time from diagnosis to negative culture conversion, but data with regard to its impact on treatment outcomes has so far been controversial [28,29]. In a large retrospective study conducted in South Africa, a reduction in the mortality rate in drug-susceptible patients from 14.9% to 9.8% (p <0.001) as well as improvement in treatment success from 71.4 to 84.6% (p <0.001) was seen after 5 years of using Xpert in TB diagnosis [30]. In other studies conducted in settings with medium and high TB and MDR-TB incidence, including one report from Kyiv (Ukraine), routine use of the Xpert MTB/RIF assay was not associated with better outcomes, or only marginal improvements have been observed [7e9,29].…”
Section: Discussionmentioning
confidence: 99%
“…GeneXpert MTB/RIF System (Cepheid, Sunnyvale, CA, Xpert) was launched in 2011 and gradually scaled up nationwide with all smear microscopy laboratories having instruments placed by 2013 10 . Studies have shown that Xpert analyser’s implementation increased both the proportion of individuals initiating TB treatment and the proportion who received a microbiological TB diagnostic test 11 , 12 .…”
Section: Methodsmentioning
confidence: 99%